Stages of formation and further development of Eurasian Economic Union legal acts system - Amirbek, K.S.; Lavnichak, A. (KSU publ., 2019)
This article sets the task to consider the main issues of the formation and development of the legal framework of the regional integration association of states — the Eurasian Economic Union (EAEU). The development of international economic integration is impossible without a legal framework, since it is through bilateral and multilateral treaties, as well as domestic legislation, that the states parties of international economic integration carry out political decisions and ideas into real life. Prospects of Eurasian Economic Union development require an analysis of new approaches to integration interaction, as well as the solution of certain legal problems. First of all, it concerns the legal support of the functioning of both the EAEU itself and the enactment of acts of its bodies. This article focuses on solving many legal problems in the framework of the implementation of customs cooperation between the Member States of the Union, as well as the adoption of national acts, the introduction of changes and amendments to national legislation. The work says that it is necessary to clearly define the system of views mutually agreed by the EAEU member states on their common goals and priorities for the development of the Union’s legal framework in the sphere of customs. Special attention is paid to the formation of the legal framework of the EAEU, the significance and structure of the legal framework of the EAEU is analyzed. Based on the analysis of international experience of regional integration organizations, the difficulties of forming of common market, common borders, legal system, common currency, trade and economic policy, etc., and ways to solve these problems are revealed. The authors notes that the internal economic systems of sovereign subjects of international law go to interact with each other, uniting among themselves in the Common Economic Space, which is a manifestation of the globalization of the international economic space. The article states that the relations of domestic economies in different parts of the international community go at different speeds. If in some states disintegration processes are developing rapidly, in certain territories sovereign subjects of international law take the strategic course for accelerated domestic economic relations.
Keywords: interstate economic integration; Eurasian theory; Customs Union (CU); Common Economic Space (CES); Eurasian Economic Union (EAEU); formation of the legal framework of the EAEU; sources of law of the EAEU; EAEU bodies; international legal personality of the EAEU; Customs Code of the EAEU (TCA EAEU); decisions of the Eurasian Economic Commission (EEC)